Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

Enzymatic synthesis of oligodextran with prebiotic potential by a recombinant dextransucrase from Latilactobacillus sakei L3 - Binbin Wang; Linlin Hao; Kaiyue Zuo; Xiaojing Liu; Huimin Yao; Weizhong Liu; Fangkun Zhao; Lei Pan; Baomei Wu (Carbohydrate Polymers, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

Seismic performance of a new type of sliding-rolling friction composite isolation bearing - Bo Liu; Danguang Pan; Congbo Song; Linlin Liu; Guowei Ni (Earthquake Engineering and Engineering Vibration, 2026)

Field study on the occurrence and risk assessment of haloacetamides in drinking water systems - Ying Yu; Ruya Chen; Linlin Pan; Baoyou Shi (Journal of Environmental Chemical Engineering, 2025)

Ultrasensitive, signal-complementary piezo-capacitive pressure sensor for complex physiological monitoring and HMI - Daojian Su; Linlin Jiang; Zijun Pan; Changhong Yang; Chang Liu; Rongxiao Liu; Tong Liu; Xin He; Shifeng Huang; Zhenxiang Cheng (Chemical Engineering Journal, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

A Study on Energy Loss and Transient Flow Characteristics of a Large Volute Centrifugal Pump During Power-Off Process Under Cavitation Conditions - Qingzhao Pang; Desheng Zhang; Gang Yang; Xi Shen; Qiang Pan; Linlin Geng; Qinghui Lu (Journal of Marine Science and Engineering, 2025)
A novel pumped storage system using centrifugal pumps to transfer water between reservoirs in coastal hydropower plants has significantly mitigated grid instability. However, frequent start–stop operations of large vertical centrifugal pumps, which serve as the core equipment, severely affect the operational stability of these systems. In this study, the intrinsic connection between the cavitating flow field and irreversible losses during the process was analyzed using the entropy production theory. The time–frequency characteristics of pressure pulsation in pump were analyzed by using the continuous wavelet transform. The results indicate that with the reduction in the flow rate and rotational speed, the sheet cavitation at the impeller inlet rapidly weakens until it vanishes. The cavity cavitation within the draft tube commences to emerge in the turbine mode. Separation vortices are formed due to the mismatch in the flow angle at the impeller outlet. These vortices induce local cavitation, causing both a rapid energy loss increase and high-amplitude, low-frequency pressure pulsations. During transient processes, flow instabilities induce high-amplitude, low-frequency pressure pulsations within the stay vane region, with maximum amplitude attained during runaway condition. The research results provide a theoretical foundation for the stable operation of centrifugal pumps.

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A nano-pesticide with low toxicity for earthworms obtained by immobilizing avermectin onto Mg/Al layered double hydroxides - Linlin Shi; Fengshou Dong; Jun Xu; Xiaohu Wu; Yongquan Zheng; Xinglu Pan (Environmental Pollution, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Identifying spatially targeted organic fertilizer subsidies for water pollution control: An interactive hydro-economic model - Shuping Wang; Pan Yang; Qian Tan; Linlin Yao; Cangbai Li (Water Research, 2025)

Performance and mechanism of tris(2-chloropropyl) phosphate (TCPP) removal in an iron-carbon microelectrolysis constructed wetland system - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Chemical Engineering Journal, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

From field to table: Reducing residual toxicity and risk of four pesticides via washing and blanching of cowpea (Vigna unguiculata (L.) Walp.) - Shuangwei Zhang; Yajing Guo; Shanshan Zhu; Linlin Guo; Xinglu Pan; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiaohu Wu (Food Chemistry, 2025)

Enhancing compost quality: Biochar and zeolite's role in nitrogen transformation and retention - Jiaying Mi; Linlin Hou; Yiming Hou; Caihong Song; Lina Pan; Zimin Wei (Science of The Total Environment, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

A comprehensive review on iron‒carbon microelectrolysis constructed wetlands: Efficiency, mechanism and prospects - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Water Research, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

The mediating role of abnormal ZEB1 methylation in the association between nickel exposure and non-syndromic orofacial cleft - Yongyan Chen; Yaquan Pan; Lijun Liu; Yingnan Guo; Lei Jin; Aiguo Ren; Linlin Wang (Reproductive Toxicology, 2024)

Iron-nitrogen coupling mediates soil microbial community composition and gene expression during the formation of rusty root in Panax ginseng from three northeast provinces in China - Qiao Jin; Linlin Zhang; Keming Cao; Xiaoxi Pan; Zhengbo Liu; Yiming Guan; Xiangxi Zuo; Yayu Zhang; Qiuxia Wang (Journal of Environmental Chemical Engineering, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

Elevated lead mobility in sediments of a eutrophic drinking water reservoir during spring and summer seasons: Insights from isotopic signatures - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Ke Pan; Yinan Deng; Linlin Jiao; Zhen Zhang; Shanshan Chen; Tianxiang Xia (Journal of Hazardous Materials, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Imbalances in the gut microbiota and metabolome are associated with functional constipation in pregnancy - Ruili Pan; Ying Chen; Guopeng Lin; Haojue Wang; Xiaopeng Xu; Linlin Wang; Peijun Tian; Jianxin Zhao; Wei Chen; Gang Wang (Food Bioscience, 2024)

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Identification of optimal organic fertilizer subsidy policies under dual uncertainty via a self-calibrated fuzzy-boundary interval programming method - Shuping Wang; Pan Yang; Qian Tan; Linlin Yao (Journal of Cleaner Production, 2024)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Assessment on the stereoselective behavior of cyflumetofen to earthworms (Eisenia foetida): Degradation, bioaccumulation, toxicity mechanism, and metabolites - Linlin Shi; Chao Shen; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Science of The Total Environment, 2023)

Systematic assessment of cyflumetofen toxicity in soil-earthworm (Eisenia fetida) microcosms - Linlin Shi; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Journal of Hazardous Materials, 2023)

Dual-response near-infrared fluorescent probe for detecting cyanide and mitochondrial viscosity and its application in bioimaging - Wei Pan; Linlin Han; Xiaoqun Cao; Shili Shen; Xianhong Pang; Yan Zhu (Food Chemistry, 2023)

Comparison and quantification of estrogen receptor-mediated responsiveness to endocrine disruptors in bivalves by using complementary model and a novel yeast assay approach - Liru Liu; Jingjing Miao; Peipei Liu; Anran Zhao; Linlin Yao; Luqing Pan (Environmental Pollution, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Different nitrogen fertilizer application in the field affects the morphology and structure of protein and starch in rice during cooking - Shijie Shi; Gaoyu Zhang; Linlin Chen; Wenhui Zhang; Xiaodong Wang; Keqiang Pan; Lina Li; Jing Wang; Juan Liu; Cougui Cao; Yang Jiang (Food Research International, 2023)

Abnormal Level of Manganese, Iron, Iodine, and Selenium in the Hair of Children Living in Kashin–Beck Disease Endemic Areas - Feng’e Zhang; Cuiyan Wu; Pan Zhang; Xi Wang; Peilin Meng; Sijia Tan; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Chromosome-Level Genome Assembly of Acanthogobius ommaturus Provides Insights Into Evolution and Lipid Metabolism - Yu Pan; Zhicheng Sun; Tianxiang Gao; Linlin Zhao; Na Song (Frontiers in Marine Science, 2022)
Acanthogobius ommaturus is a large, fast-growing annual fish widely distributed in coastal and estuarine areas. The adults will die after breeding, and its life cycle is only 1 year. The first chromosome-level genome assembly of A. ommaturus was obtained by PacBio and Hi-C sequencing in this study. The final genome assembly after Hi-C correction was 921.49 Mb, with contig N50 and scaffold N50 values of 15.70 Mb and 40.99 Mb, respectively. The assembled sequences were anchored to 22 chromosomes by using Hi-C data. A total of 18,752 protein-coding genes were predicted, 97.90% of which were successfully annotated. Benchmarking Universal Single-Copy Orthologs (BUSCO) assessment results for genome and gene annotations were 93.6% and 84.6%, respectively. A. ommaturus is phylogenetically closely related to Periophthalmodon magnuspinnatus and Boleophthalmus pectinirostris , diverging approximately 31.9 MYA with the two goby species. The A. ommaturus genome displayed 597 expanded and 3,094 contracted gene families compared with the common ancestor. A total of 1,155 positive selected genes (PSGs) ( p < 0.05) were identified. Based on comparative genomic analyses, we obtained several expanded genes such as acsbg2 , lrp1 , lrp6 , and znf638 involved in lipid metabolism. A total of twenty candidate genes were identified under positive selection, which associated with lifespan including ercc6 , igf1 , polg , and tert . Interspecific collinearity analysis showed a high genomic synteny between A. ommaturus and P. magnuspinnatus . The effective population size of A. ommaturus decreased drastically during 200–100 Ka because of Guxiang ice age and then increased gradually following warm periods. This study provides pivotal genetic resources for in-depth biological and evolutionary studies, and underlies the molecular basis for lipid metabolism.

Occurrence, spatial distribution, source, and ecological risk assessment of organochlorine pesticides in Dongting Lake, China - Fengmei Cao; Zhaozhao Li; Qi He; Shaoyong Lu; Pan Qin; Linlin Li (Environmental Science and Pollution Research, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Quantitative assessment on soil concentration of heavy metal–contaminated soil with various sample pretreatment techniques and detection methods - Fei Pan; Yong Yu; Lei Yu; Hailan Lin; Yeyao Wang; Linlin Zhang; Dawei Pan; Rilong Zhu (Environmental Monitoring and Assessment, 2020)

The immune response to a recombinant Lactococcus lactis oral vaccine against foot-and-mouth disease virus in mice - Xinsheng Liu; Linlin Qi; Jianliang Lv; Zhongwang Zhang; Peng Zhou; Zhongyuan Ma; Yonglu Wang; Yongguang Zhang; Li Pan (Biotechnology Letters, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Effect of supersaturation on the oral bioavailability of paclitaxel/polymer amorphous solid dispersion - Linlin Miao; Yuheng Liang; Wenli Pan; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Xing Tang (Drug Delivery and Translational Research, 2019)

Time-Dependent Lactate Production and Amino Acid Utilization in Cultured Astrocytes Under High Glucose Exposure - Dan Wang; Liangcai Zhao; Hong Zheng; Minjian Dong; Linlin Pan; Xi Zhang; Huajie Zhang; Hongchang Gao (Molecular Neurobiology, 2018)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

Impact of atmospheric and oceanic conditions on the frequency and genesis location of tropical cyclones over the western North Pacific in 2004 and 2010 - Pan Song; Jiang Zhu; Zhong Zhong; Linlin Qi; Xiaodan Wang (Advances in Atmospheric Sciences, 2016)

Transcriptomic analysis reveals key regulators of mammogenesis and the pregnancy-lactation cycle - YuanYuan Zhou; Wei Gong; JingFa Xiao; JiaYan Wu; LinLin Pan; XiaoNuan Li; XuMin Wang; WeiWei Wang; SongNian Hu; Jun Yu (Science China Life Sciences, 2014)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

Identification and Analysis of Muscle-Related Protein Isoforms Expressed in the White Muscle of the Mandarin Fish (Siniperca chuatsi) - Guoqiang Zhang; Wuying Chu; Songnian Hu; Tao Meng; Linlin Pan; Renxue Zhou; Zhen Liu; Jianshe Zhang (Marine Biotechnology, 2011)